Secure Reversible Data Hiding in Encrypted Images by Allocating Memory before Encryption via Security keys - Jambhulkar, Priya; Pardhi, P.R. (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
Digital image and information embedding system have number of important multimedia applications. Recently, attention is paid to reversible data hiding (RDH) in encrypted images is more, since it maintains the excellent property that the original cover can be lossless recovered after embedded data is extracted while protecting the image content’s confidentiality. RDH is a technique used to hide data inside image for high security in such a way that original data is not visible. All previous methods embed data by reversibly vacating room from the encrypted images, which may be subject to some errors on data extraction and/or image restoration. In this paper, we propose another method in which we simply encrypt an image without its header by using our own algorithm. And thus it is easy for the data hider to reversibly embed data in the encrypted image. The proposed method can achieve real reversibility, that is, data extraction and image recovery are free of any error.